Review on Emission Reduction Control Path Based on Modern Project Management Method for Large Integrated Energy Groups in A Carbon Constrained World - Zhao, Shengguang; Lu, Yiqiong (Journal of Environmental Accounting and Management, 2026)
Actively participating in the global process on climate change, thoroughly implementing the national outline on climate change, and fully imple-menting clean energy development strategy to control the total amount of carbon emissions and reduce carbon emissions intensity, are the inevi-table requirement of large domestic clean energy enterprise development currently. Aimed at how to carry out related work in a carbon con-strained world, this paper shows systematic analysis of what large inte-grated energy enterprises need to do, how to do, who is going to do, and effective measures to be taken to promote and realize the low carbon development.